2022
DOI: 10.3389/fphar.2022.1019594
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of astragalus membranaceus and its bioactive compounds against the intestinal inflammation in Drosophila

Abstract: Inflammatory bowel disease (IBD) is characterized by chronic and relapsing intestinal inflammation, which currently lacks safe and effective medicines. Astragalus membranaceus (AM), also named Huangqi, is one of the most commonly used fundamental herbs in China. Here, we aimed to investigate mechanism and bioactive compounds of AM on treating sodium dodecyl sulfate (SDS)- induced colitis in Drosophila flies. Our data showed that AM extract (AME) supplementation had no toxic effect in flies, and protected flies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…The preservation of ISCs’ stemness is required for repair of the intestinal damage because ISCs may produce a variety of intestinal epithelial cell types. In the current study, we found that SC06 dramatically decreased ileum inflammation and enhanced the intestinal physical barrier, likely via the action of ISC proliferation. Our findings demonstrated that SC06 administration substantially elevated the mRNA levels of ISCs maker genes in the LPS challenge pigs.…”
Section: Discussionmentioning
confidence: 54%
“…The preservation of ISCs’ stemness is required for repair of the intestinal damage because ISCs may produce a variety of intestinal epithelial cell types. In the current study, we found that SC06 dramatically decreased ileum inflammation and enhanced the intestinal physical barrier, likely via the action of ISC proliferation. Our findings demonstrated that SC06 administration substantially elevated the mRNA levels of ISCs maker genes in the LPS challenge pigs.…”
Section: Discussionmentioning
confidence: 54%
“…[32] Inflammation: Huangqi mediated multiple signaling pathways to exert anti-inflammatory effects, such as mediating the TLR-4/ NF-kb p65 pathway [33] and regulating the Wnt/β-catenin signaling pathway, [34] down-regulating the expression of inflammatory factors IL-1, IL-6, and TNF-α, and inhibiting the JNK signaling pathway associated with oxidative stress, reducing the expression of transcriptional level of the puc gene. [35] These 3 pathological processes may be the main pharmacological mechanism of Huangqi, which was also the focus of the research area of Huangqi.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental experiments were performed according to previous report 28 . Sixty fly eggs per tube were transferred to the vials containing basal medium or basal medium with COS. COS was added to basal medium to final concentrations (w/v) of 0.625, 1.25, and 2.5 mg/mL according to previous study, 26 defined as COS‐L, COS‐M, and COS‐H, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The safety of drugs can be evaluated by the developmental status of flies. 28 The lifespan, the pupation rate, the emergence rate, and the average weight of flies fed with or without COS were analyzed as shown in Figure 2. The results showed that 0.625, 1.25, and 2.5 mg/mL COS significantly extended the lifespan of female flies (Figure 2A) and had no significant effect on the lifespan of male flies (Figure 2B).…”
Section: Cos Has No Toxic Effect On Fliesmentioning
confidence: 99%
See 1 more Smart Citation